THE GREATER OMENTUM CAN BE A STEM CELL DONOR TO THE ISCHEMIC MYOCARDIUM? - Kubrusly , Fernando Bermudez (2024)
Introduction: Recent progress in the bioengineering of cardiac grafts offers a new therapeutic modality for the regeneration of cardiac tissue after myocardial infarction. CD34 is a marker that expresses all hematopoietic and endothelial precursor cells, and functions as a cell adhesion factor. The antibody corresponding to this marker is used in immunohistochemistry to evaluate the formation of new vessels and the presence of stem cells. Objective: To evaluate the effectiveness of omentopexy in neovascularization and stem cells. Methods: Review collecting information published on selected virtual platforms (SciELO – Scientific Electronic Library Online, Google Scholar, Pubmed and Scopus). The search began with descriptors related to the topic, identified through DeCS/MESH in the following: “myocardial ischemia; myocardial revascularization; omentopexy; immunohistochemistry; CD34; stem cells”. They were read by title and summary, with an AND or OR search followed by the full reading of those most closely related to the topic. A total of 23 articles were included. Results: The greater omentum has a remarkable clinical property in containing sites of tissue damage. It increases its tissue volume in response to foreign and inflammatory particles involving several immunomodulatory cells with progenitor cells, in a process called “omentum activation”. Conclusion: Cardio-omentopexy associated with mechanical abrasion and myocardial perforations proves to be efficient in inducing neovascularization. The greater omentum promotes stem cells - confirmed by CD34 -, demonstrating great potential as a future therapy to restore areas of ischemic myocardium.